Risk factors of systemic inflammatory response syndrome after minimally invasive percutaneous nephrolithotomy with a controlled irrigation pressure - Senlin Lan; Bohao Liu; Siwei Xie; Chunting Yang (BMC Urology)
Abstract Objective This study aims to identify the risk factors for systemic inflammatory response syndrome (SIRS) after minimally invasive percutaneous nephrolithotomy (PCNL) with a controlled irrigation pressure and to find which patients undergoing PCNL are likely to develop SIRS under the pressure-controlled condition. Methods A total of 303 consecutive patients who underwent first-stage PCNL in our institute between July 2016 and June 2018 were retrospectively reviewed. All the procedures were performed with an 18 F tract using an irrigation pump setting the irrigation fluid pressure at 110 mmHg and the flow rate of irrigation at 0.4 L/min. SIRS and sepsis were recorded after PCNL. The demographic data, clinical features, and test results were analyzed. Results 52 patients (17.2%) developed SIRS and only 3 patients (0.99%) further progressed to severe sepsis. The results of univariate analysis showed that the stone size, operative time, history of DM, the value of glycosylated hemoglobin, history of ipsilateral surgery, preoperative urine culture, Staghorn calculi, pelvic urine culture, stone culture, number of tracts, blood transfusion, and residual stones were found to have a significant correlation with post-PCNL SIRS (p < 0.05). In multivariate analysis, the stone size (OR = 3.743, p = 0.012), preoperative urine culture (OR = 2.526, p = 0.042), pelvic urine culture (OR = 13.523, p < 0.001), the number of access tracts (OR = 8.945, p = 0.002), blood transfusion (OR = 26.308, p < 0.001) were identified as the independent risk factors for post-PCNL SIRS. Conclusion The stone size (>4cm2), positive preoperative urine culture, positive pelvic urine culture, multiple tracts, receipt of a blood transfusion are the independent risk factors for SIRS under the pressure-controlled condition. More attention should be paid when the PCNL patients have these risk factors.